Handbook of Florida Water Regulation: Safe Drinking Water Act - Michael T. Olexa; Luke D'Isernia; Laura Minton; Dulcy Miller; Sarah Corbett (EDIS)
This handbook is designed to provide an accurate, current, and authoritative summary of the principle Federal and Florida laws that directly or indirectly relate to agriculture. This handbook should provide a basic overview of the many rights and responsibilities that farmers and farmland owners have under both Federal and Florida laws as well as the appropriate contact information to obtain more detailed information. However, the reader should be aware that because the laws, administrative rulings, and court decisions on which this handbook is based are subject to constant revision, portions of this publication could become outdated at anytime. Several details of cited laws are also left out due to space limitations. This document is FE587, one of a series of the Food and Resource Economics Department, UF/IFAS Extension. Published December 2005.